Conversational Implicature Analysis on Fast Five Movie - Sudrajat, Muhamad Donny; Winarto, Eline Rozaliya; Adiantika, Hanif Nurcholish (Ma'soem University, 2024)
Movie is a medium that can easily attract human attention, in terms of image quality and storyline. However, not everyone is aware of the hidden meaning in conversation between the actors. This research was conducted to explore the hidden meaning of the conversation in Fast Five movie. The objective of this research is to find out and analyse the types of conversational implicature in Fast Five movie. Fast Five movie was directed by Justin Lin and released in 2011. The method used in this research is descriptive qualitative method. Researcher employ himself as a research instruments by collecting, observing and analyzing the data. This research are expected to increase people’s ability to understand the hidden meaning of a conversation. Conversational implicature is divided into 2 categories, particularized implicature and generalized implicature. Besides, generalized implicature consists of indefinite implicature and scalar implicature. The result of this research are 10 data regarding Particularized Implicature, 4 data regarding Generalized Implicature, 5 data regarding Indefinite Implicature and 7 data regarding Scalar Implicature. The percentage obtained from the 4 types of Conversational Implicature are 39% found in Particularized Implicature, 15% found in Generalized Implicature, 19% found in Indefinite Implicature and 27% found in Scalar Implicature.